Meningkatkan Hasil Belajar Energi Gerak Melalui Pembelajaran Kooperatif Model STAD Pada Siswa Kelas IV SDN 1 Sungguminasa Kabupaten Gowa - Sri Hastati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
The research investigated about whether the learning outcomes of the fourth grade students of SDN 1 Sungguminasa Gowa Regency can be improved through the cooperative learning of STAD model. The aims are to overcome difficulties and determine the learning outcomes of motion energy through cooperative learning of STAD model. The hypothesis is if use the cooperative learning of STAD model, the learning outcomes of the fourth grade students will increase. The research design is qualitative with classroom action research methods. The data was collected through observation, interview, test, questionnaire, and documentation techniques, then analyzed inductively. The results showed the cooperative learning of STAD model can make the students to understand the material and improve the learning outcomes of movement energy. The test results before learning were 6 students got a score 80, 8 students got a score 60, 4 students got a score 40, and 4 students got a score 20. On the results of the action test cycle I, 15 students got a score 70 and above while 7 students scores below 70. In the action cycle II students learning outcomes increased, in which all students scored above 70 with an average value of 86.13%.